Visão Epidemiológica da Incidência de Neoplasias Malignas de Próstata - Slongo Bressan, Túlio; do Nascimento dos Santos, Marcelo; Martinez Salazar, Victor Alfonso; Abinadab Majjul Salazar, Eduardo; Martinez Salazar, Gustavo Adolfo; Sosa Cañete., Maria Zunilda; Nascimento de Souza , Nayra Lurian; Garibaldi Cucolicchio, Olívia; Toro Salazar, Nataly Alejandra; Almeida, Nixon; Damasceno Costa, Maiane; Alves Ribeiro, Maria Dandara; et al. (Brazilian Journal of Implantology and Health Sciences, 2024)
Malignant neoplasms of the prostate, also known as prostate cancer, are malignant tumors that originate in the cells of the prostate, a gland in the male reproductive system responsible for producing seminal fluid. Therefore, the epidemiological view of the incidence of malignant neoplasms of the prostate highlights that prostate cancer is one of the most common neoplasms among men, with a higher incidence in individuals over 50 years of age. This is a descriptive study, conducted using information on annual hospitalization rates, extracted from SIH/DATASUS, according to place of residence, starting in 2008, using the International Classification of Diseases (ICD-10): malignant neoplasm of the prostate is C61. The following variables were used: year of care, all regions of the country, specific age range of 30 to 80 years or older and race/color. According to the analysis, there are 168,427 hospitalizations for prostate cancer with a prevalence of 36,779 in 2023, in the Southeast region with 85,005, in the age group from 60 to 69 with 63,959 hospitalizations and the race/yellow color 71,899. The study highlighted that the risk factors for prostate cancer include age, family history and comorbidities. Resistance to prostate exams is related to cultural and masculinity issues. Continuous prevention campaigns, with the support of Primary Care, are essential to raise awareness and overcome the taboo about the exam.